Biological Reviews - Biological Reviews (Wiley, 2026)
Biological Reviews is a unique journal covering the entire range of the biological sciences. Our research is aimed at non-specialist biologists as well as researchers in the field. Our research includes introductions to particular fields, defining the state of the art, and drawing attention to gaps in knowledge. Our authors gain international exposure with global circulation when publishing in Biological Reviews. Published on behalf of the Cambridge Philosophical Society.
FI 2.94
Q1
Keywords: Life Sciences; Ciencias de la vida; Acuerdos transformativos; Transformative agreements; Ciencias biológicas (revisiones sintéticas); Marcos teóricos y conceptuales en biología; Síntesis de literatura y estado del arte en temas biológicos